Perancangan Ulang UI-UX Desain Website BKKBN Provinsi Sumatera Selatan dengan Metode Design Thinking - Dea Salsa Bila; Dwi Rosa Indah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Every year, the BKKBN website for South Sumatra Province experiences development from the center without conducting a direct survey of the website's feasibility with its users. At present, the South Sumatra Provincial BKKBN employees feel that the South Sumatra Provincial BKKBN website has an unattractive appearance and is not user-friendly. The appearance of the user interface and the user experience are things that must be considered when building a website. This display will affect the user's decision to reuse the website or not. This study designed the UI/UX design for the BKKBN website for South Sumatra Province using the design thinking method. Prior to designing, a website evaluation test will be carried out using the system usability scale (SUS) method to measure the usability value of the website. The results of the average test value using the system usability scale (SUS) can be said to be good and accepted by users if the test results are  68. This study found that the results of usability evaluation tests before design improvements were carried out had an average value of SUS 65, and after improvements were made, UI/UX design using the design thinking method resulted in an average SUS score of 81.5